2005
DOI: 10.1159/000085918
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Testicular Microlithiasis

Abstract: Introduction: Testicular microlithiasis is an uncommon condition characterized by calcifications within the seminiferous tubules. The true prevalence in a normal population has not been defined. Methods: A review of the literature with emphasis on the connection between testicular microlithiasis and testicular malignancy was carried out. Results: Testicular microlithiasis is associated with different testicular pathologies, including testicular cancer. However, a direct causative connection between testicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
7
0
2
Order By: Relevance
“…Testicular microlithiasis (TM) is characterised by the presence of microcalcification within the seminiferous tubules. In the normal human population the incidence is between 1.5 and 5.6% [ 1 - 3 ] and in itself microlithiasis is benign but there may be significant association with malignant conditions such as testicular germ cell tumors (TGCT) [ 4 - 7 ] and other conditions such as cryptorchidism, varicocele, infertility, and testicular torsion [ 8 , 9 ]. In addition, it has been suggested that there may be a genetic predisposition to TM which is linked to TGCT formation so that identifying the underlying causes of microlithiasis may help identify susceptibility factors for TGCTs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Testicular microlithiasis (TM) is characterised by the presence of microcalcification within the seminiferous tubules. In the normal human population the incidence is between 1.5 and 5.6% [ 1 - 3 ] and in itself microlithiasis is benign but there may be significant association with malignant conditions such as testicular germ cell tumors (TGCT) [ 4 - 7 ] and other conditions such as cryptorchidism, varicocele, infertility, and testicular torsion [ 8 , 9 ]. In addition, it has been suggested that there may be a genetic predisposition to TM which is linked to TGCT formation so that identifying the underlying causes of microlithiasis may help identify susceptibility factors for TGCTs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that TM is more frequent among men with infertility and those with cryptorchidism (Thomas et al, 2000; Zastrow et al, 2005), both of which are established TGCT risk factors. In our study, only six men reported infertility, all of whom had TGCT, and all but one had TM.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of these lesions is not well understood, but they are proposed to be caused by degeneration of the seminiferous tubules (Dagash & Mackinnon, 2007). A number of medical conditions have been associated with TM, including cryptorchidism, varicocele, infertility and testicular torsion (Thomas et al, 2000; Zastrow et al, 2005). Importantly, numerous cross- sectional studies have shown an association between TM and testicular malignancy; in those studies, 8–54% of men with TM had concomitant TGCT (Bach et al, 2001; Ganem et al, 1999; Lam et al, 2007; Otite et al, 2001; Parenti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…La existencia de neoplasias testiculares desarrolladas tras el diagnóstico de MT 27,28 abre una controversia sobre si se debe considerar a esta entidad como una lesión premaligna, y sobre cuál debe ser el seguimiento de los pacientes una vez diagnosticados, y sobre la necesidad o no de realizar pruebas más agresivas, como la biopsia 29 . En revisiones amplias [30][31][32][33][34] queda demostrado que no hay evidencia para sugerir que las MT deban ser consideradas como una entidad premaligna por sí misma y que representan más bien una manifestación de una disfunción testicular. La asociación de MT a condiciones que ya de por sí aumentan el riesgo de tumor testicular (criptorquidia), favorecería la hipótesis más probable acerca de su origen en la cual se considera que tanto la MT como la aparición de neoplasias sea debida aun sustrato etiológico común como podría ser la atrofia, isquemia y degeneración del tejido testicular disgenético 13 .…”
Section: Discussionunclassified